2018
DOI: 10.1007/s00787-018-1138-8
|View full text |Cite
|
Sign up to set email alerts
|

Attention profiles in autism spectrum disorder and subtypes of attention-deficit/hyperactivity disorder

Abstract: Attention problems are observed in attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). Most neuropsychological studies that compared both disorders focused on complex executive functions (EF), but missed to contrast basic attention functions, as well as ASD- and ADHD subtypes. The present study compared EF as well as basic attention functioning of children with the combined subtype (ADHD-C), the predominantly inattentive subtype (ADHD-I), and autism spectrum disorder without ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…The effects during school classes may be much more significant if concentration in cycles of 45 min is required. Our findings are consistent with previous studies on vigilance deficits in children with ADHD using the paradigm of continuous performance, both in traditional tests and virtual reality (VR; Berger et al, 2013 ; Boxhoorn et al, 2018 ; Cueli et al, 2015 ; Egeland et al, 2009 ; González-Castro et al, 2013 ). Interestingly, according to recent studies, CPTs in VR technology show greater diagnostic power (sensitivity and specificity) regarding ADHD compared to standard computer tests ( Areces et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The effects during school classes may be much more significant if concentration in cycles of 45 min is required. Our findings are consistent with previous studies on vigilance deficits in children with ADHD using the paradigm of continuous performance, both in traditional tests and virtual reality (VR; Berger et al, 2013 ; Boxhoorn et al, 2018 ; Cueli et al, 2015 ; Egeland et al, 2009 ; González-Castro et al, 2013 ). Interestingly, according to recent studies, CPTs in VR technology show greater diagnostic power (sensitivity and specificity) regarding ADHD compared to standard computer tests ( Areces et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…These tasks are characterized by a low occurrence probability of a signal according to the criterion and an uncomplicated information selection rule. Existing studies have indicated vigilance deficiency in children with ADHD ( Berger et al, 2013 ; Boxhoorn et al, 2018 ; Egeland et al, 2009 ). Continuous performance tests tests are a common neuropsychological tool used in disorder prediction ( Berger et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, one study is not enough to infer a pattern concerning the role of context. Of note, not only the presence or absence of context, but also the type of context may matter, because context with a large amount of information could hamper comprehension by overloading participants' working memory and affecting attention (see Boxhoorn et al, 2018;Pennington & Ozonoff, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive control abnormalities, also termed under the umbrella "executive functions", are among the main key features of neurodevelopmental disorders such as autism spectrum disorder (ASD), Intellectual Disability (ID), attention deficit hyperactivity disorder (ADHD) and schizophrenia (Boxhoorn et al, 2018;Conzelmann et al, 2016;Ehlis et al, 2011;Filipe et al, 2018;Garon et al, 2018;Hronis et al, 2017;Joyce et al, 2002;Karalunas et al, 2018;Kerns et al, 2008;Lifshitz et al, 2016;Managó et al, 2016;More and Jensen, 2014;More et al, 2017;Ouhaz et al, 2018;Scheggia et al, 2014;Sidorov et al, 2018;Weinberger et al, 1986). Cognitive control deficits also are described for individuals with prefrontal cortex lesions suggesting that the frontal lobe system area is critically important for this behavior (Miller and Cohen, 2001).…”
Section: Cognitive Controlmentioning
confidence: 99%